2018
DOI: 10.17235/reed.2018.5524/2018
|View full text |Cite
|
Sign up to set email alerts
|

Routine lower gastrointestinal endoscopy for radiographically confirmed acute diverticulitis. In whom and when is it indicated?

Abstract: routine colonoscopy is advisable after a complicated diverticulitis event but its recommendation is unclear with regard to uncomplicated episodes. Colonoscopy is safe even when performed early. The overall quality is low but may be optimized via a subsequent endoscopy, two months after a diverticulitis diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Multidetector CT can obtain thinner sections and has a better resolution and images of higher quality [6,17]. It is presently considered the best imaging technique for the diagnosis of AD and its complications, with a sensitivity and specificity of 94% and 99% respectively [4,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multidetector CT can obtain thinner sections and has a better resolution and images of higher quality [6,17]. It is presently considered the best imaging technique for the diagnosis of AD and its complications, with a sensitivity and specificity of 94% and 99% respectively [4,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Colonic diverticular disease is a pathology with a high prevalence throughout the world, being most prevalent in developed countries, and whose incidence is increasing. It is estimated that 5-10% of the population >45 years old and approximately 80% of those >85 years old suffer this pathology [1-4]. The economic impact due to episodes of acute diverticulitis (AD) has been estimated at approximately $3,500-12,800 for each patient admitted, depending on the length of stay and the type of treatment performed [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,30,35,49,50,59,60,62,63,78,85,89 There were 13 296 patients from 65 studies who underwent a follow up colonoscopy. 6,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][67][68][69][70][71][72][73][74][75][76][77][78][79][81][82][83][84][85][86][87][88]…”
Section: Study Demographicsmentioning
confidence: 99%
“…6,25,40,41,44,49,58,63,65,78 Follow up was greater than 80% in 25 studies. 25,29,[31][32][33]39,41,44,45,49,[53][54][55]60,61,63,67,71,74,[77][78][79][80]86,89 Primary study outcomes Colorectal cancers were identified in 2.0% (95% CI 1.67-2.40) of patients undergoing interval colonoscopy or flexible sigmoidoscopy after acute diverticulitis in 68 studies (see Table 1). 6, The distribution of cancers was 27.9% sigmoid/descending colon, 9.0% proximal to splenic flexure, 3.7% in rectum and 59.4% with location not reported.…”
Section: Study Demographicsmentioning
confidence: 99%